Sluggish institutions in a dynamic world: can unions and industrial competition coexist? - Barry T. Hirsch (Institute for the Study of Labor (IZA), 2007)
During the 1930s and 1940s, collective bargaining emerged as the workplace governance norm in much of the U.S. industrial sector. Following its peak in the 1950s, union density in the U.S. private sector fell steadily, to only 7.4 percent in 2006. Governance shifted from a formalized union norm to one of constrained managerial discretion. In competitive and dynamic economic environments, a union tax on company earnings and slow response to economic shocks combine to produce poor performance by union companies. Two industries - automotives and airlines - are used to illustrate these points. If worker-based institutions are to flourish, they must add value and permit companies to perform at levels similar to those obtained under evolving nonunion governance norms.
Keywords: 330; Gewerkschaft; Arbeitsbeziehungen; Governance-Ansatz; Gewerkschaftlicher Organisationsgrad; Unternehmensentwicklung; Internationaler Wettbewerb; Kraftfahrzeugindustrie; Luftverkehrsgesellschaft; USA